A modified-set partitioning in hierarchical trees algorithm for real-time image compression - Akter, M.; Reaz, M. B. I.; Mohd-Yasin, F.; Choong, F. (MAIK NAUKA/INTERPERIODICA/SPRINGER, 2008)
Among all algorithms based on wavelet transform and zerotree quantization, Said and Pearlman's set partitioning in hierarchical trees (SPIHT) algorithm is well known for its simplicity and efficiency. SPIHT's high memory requirement is a major drawback to hardware implementation. In this study, we present a modification of SPIHT named modified SPIHT (MSPIHT), which requires less execution time at a low bit rate and less working memory than SPIHT. The MSPIHT coding algorithm is modified with the use of one list to store the coordinates of wavelet coefficients instead of three lists of SPIHT; defines two terms, number of error bits and absolute zerotree; and merges the sorting pass and the refinement pass together as one scan pass. Comparison of MSPIHT with SPIHT on different test image shows that MSPIHT reduces execution time at most 7 times for coding a 512 x 512 grayscale image; reduces execution time at most 11 times at a low bit rate; saves at least 0.5625 MB of memory; and reduces minor peak signal-to noise ratio (PSNR) values, thereby making it highly promising for real-time and memory limited mobile communications.